Remote Sensing applied to the analysis of the Heat Islands phenomenon in the city of Juazeiro do Norte - CE (Research, Society and Development, 2022)
The municipality of Juazeiro do Norte, located in the Cariri region of Ceará, is a city that has expanded considerably in recent decades. The accelerated urbanization process, without environmental planning, has increased air and surface temperatures, directly affecting the thermal comfort of the local population. Thus, the study of spatialization and seasonal behavior of this phenomenon is essential for decision-making in public policies in the city. The objective of this work, therefore, is to evaluate the effect of land use dynamics on the surface temperature of the city of Juazeiro do Norte in order to identify islands of heat and freshness in a time series (2005 to 2020) of images from the Landsat platform. To obtain the historical series of surface temperature and NDVI, images from Landsat 5, TM sensor in bands 3, 4 and 6 and Landsat 8, OLI sensor, in bands 4, 5 and 10 acquired from the United States Geological Survey (USGS) were used. As a result, heat islands were identified that involve intensely built neighborhoods with exposed soil classes, while islands of freshness make up the water bodies and the vegetation that surround them. The afforestation of the city with evergreen plants can favor the reduction of the local temperature, especially in the dry months.